Given f(x)=2x+5 and g(x)=8x+2 then what is (f−g)(−9)) ?

At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get our expert's

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions.

A community for students.

Given f(x)=2x+5 and g(x)=8x+2 then what is (f−g)(−9)) ?

Algebra
See more answers at brainly.com
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.

Get this expert

answer on brainly

SEE EXPERT ANSWER

Get your free account and access expert answers to this and thousands of other questions

@UsukiDoll think you could help please ?
first off, (f-g)(x) = f(x)-g(x) = __ ?
8x+2

Not the answer you are looking for?

Search for more explanations.

Ask your own question

Other answers:

not quite f(x) = 2x + 5 g(x) = 8x + 2 f(x) - g(x) = ?
-6x+7?
not quite, check your math one more time f(x) - g(x) = (2x + 5) - (8x + 2) = ?
-6x+3?
good! so we know that (f-g)(x) = -6x + 3 so what is (f-g)(-9)= ?
2x+14?
uh... not quite x = -9 (f-g)(x) = -6x + 3 = ?
8x+11?
x = -9 means replace "x" with "-9" whenever you see it (f-g)(x) = -6x + 3 = ?
if it's still unclear... (f-g)(x) = -6x + 3 = -6*(-9) + 3 = ?
57?
right
so thats the answer?
yes
could you help me with a few more please ? @Vocaloid
I need to get going, let me tag @Nnesha
@Nnesha think you could help me with this one please Match the correct graph to the function shown. f(x)=2sqrt3-4x +3
@Vocaloid thanks for helping. I'm super exhausted right now and just want to browse OpenStudy.

Not the answer you are looking for?

Search for more explanations.

Ask your own question